THE CRIMINAL TYPE OF DISCLOSURE OF SECRETS IN LIGHT OF THE DUTY AND NOTARIAL OBLIGATION TO KEEP THE SECRET IN COSTA RICA - Madrigal Córdoba, Silvia María (2025)
Professional secrecy in the relationship between a notary and their users constitutes a duty and a guarantee, although for some, it seems paradoxical, especially when notarial activity is reduced to what is recorded in the protocol and various registries. Article 38 of the Notarial Code and Article 20 of the Deontological Guidelines of the Costa Rican Notary regulate the obligation to keep the secrecy of out-of-the-protocol statements. Notarial practice currently faces new goals and challenges, largely due to the proliferation of criminal conducts such as money laundering and drug trafficking. The notarial function is key in the transfer of assets, which has led to professionals in this branch of law to be considered a vulnerable group that must adopt measures in accordance with the international and national strategies to fight against these social problems. The Financial Action Task Force (FATF) issued several recommendations, some of which apply to notaries. Costa Rica has adopted these recommendations, which have led to the inclusion of new obligations and measures, in the case under study, that apply to notaries. As part of these measures, the Área de Prevención was created within the Dirección Nacional de Notariado (National Notary Directorate, DNN by its acronym in Spanish), responsible for supporting, supervising, and inspecting these professionals. The recommendations include references to professional secrecy for lawyers and notaries. The Costa Rican Criminal Code penalizes the disclosure of secrets by professionals, such as notaries, who exert a delegated public function but are not considered public officials solely for being notaries, as analyzed by the jurisprudence of the Constitutional Court. The analysis of the criminal offense will be addressed after establishing general aspects of notarial practice as a prelude to a better understanding of the crime addressed from the notarial function.